Investigation and Optimization of Neon Soft X-ray of the INTl Plasma Focus at 12 kV - Jr Apilado Roy, Federico (2015)
This thesis describes the theoretical and experimental investigations of the x-ray (specifically neon soft x-ray) properties and the plasma dynamics of the INTl